Prototype Development of Android-Based Thesis Information System at Institute Informatics and Business (IIB) Darmajaya Bandar Lampung - Arman Suryadi Karim; Sutedi Sutedi; Melda Agarina (Prosiding International conference on Information Technology and Business (ICITB), 2019)
The rapid progress of Android-based mobile device technology has propelled the development of various applications that add diversified functions to mobile devices. Advanced systems in Android-based applications have also been utilized in many different sectors of life, including in education, from K-12 to university. Such advanced systems will be able to effectively solve distance and time limitations. This study tries to develop an Android-based system of thesis/final project consultation service that will help us solve some issues in availability schedule between students and lecturers. It is not designed to replace conventional consultation service, but rather to serve as an additional channel that connects students and lecturers in planning the thesis/final project consultation process. The ultimate aim, therefore, is to smooth the way for consultation process and to help more students complete their theses/final projects without considerable delays. In addition, the onlineconsultation system will minimize paper consumption since it offers a paperless procedure.Keywords: Android, consultation, thesis